2009
DOI: 10.2164/jandrol.108.007245
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Testosterone Deficiency: III. Cardiovascular Disease

Abstract: A considerable body of evidence exists suggesting that androgen deficiency contributes to the onset, progression, or both of cardiovascular disease (CVD). The aim of this review is to evaluate the relationships between testosterone (T) deficiency and risk factors of CVD and to discuss the implications of androgen deficiency in men with cardiovascular risk factors. The relationship between androgen deficiency and endothelial function, lipid profiles, inflammatory responses, altered vascular smooth muscle reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(167 citation statements)
references
References 183 publications
4
155
0
8
Order By: Relevance
“…Recent studies also suggest a beneficial role for testosterone in endothelial regeneration. 26 Testosterone replacement in hypogonadal men results in an increase in the number of circulating endothelial progenitor cells. 27 This increase is androgen receptor mediated (not a result of rise in estrogen levels) as this event is abolished by androgen receptor antagonists.…”
Section: Vascular Tone and Endothelial Functionmentioning
confidence: 99%
“…Recent studies also suggest a beneficial role for testosterone in endothelial regeneration. 26 Testosterone replacement in hypogonadal men results in an increase in the number of circulating endothelial progenitor cells. 27 This increase is androgen receptor mediated (not a result of rise in estrogen levels) as this event is abolished by androgen receptor antagonists.…”
Section: Vascular Tone and Endothelial Functionmentioning
confidence: 99%
“…Consequently, testosterone determination is mandatory in the differential diagnosis of male impotence. 5 Testosterone level is related to other entities not related with the sexual sphere such as diabetes mellitus (DM), 6 metabolic syndrome (MS), 7 heart disease 8 and even mortality. 9 MS is a cluster of risk factors that includes abdominal obesity, increased blood fasting glucose, dyslipidemia and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of testosterone and other androgens in CVD risk in men is controversial [49,50], recent clinical, epidemiological, cellular and animal studies have demonstrated that similar to the protective effects of E2 in women, androgens can also have positive effects on the vasculature [25,31,34,51,52]. This is exemplified by the increased incidence of CV risk factors in men with hypogonadism or undergoing androgen deprivation therapy (ADT) as part of their treatment regimen for prostate cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 99%